Level of exposure and attitude of Brgy. Boulevard, Molo Residents to " Hutik sa Kagabihon. - Condez, Arden Rod B.
The level of exposure and attitude of Brgy. Boulevard, Molo to "Hutik sa Kagabihon" was examined in this study using the one-shot survey design. Level of exposure was measured by the frequency of days spent in listening to the program. It could either be once a month or more than once a month. The attitude on the other hand was measured using the Likert Scale. Questionnaire were given out to respondents through an incidental random sampling. The researchers assured that the six zones of the locale were evenly represented. Of the 90 valid respondents, 73 or 81 were aware of the program but only 38 or 42.22 were listeners. Of the 38 respondents, 34 listened more than once a month and only four listened once a month. These 38 respondents answered to the attitude statements that determined the cognitive, affective, and behavioral attitudes towards "Hutik sa Kagabihon"., The theory used in this study was the Stimulus-Response Theory. According to this theory, exposure to a stimulus, message, or object leads to the formation of attitude or set of attitudes in an individual. Robert Zajonc's "mere exposure phenomenon" argues that mere exposure strengthens a person's response and evaluation towards an attitude object. The frequency and mean test was used to determine if the attitude of the sample is favorable or unfavorable towards the program. It was found out that the 38 respondents were favorable to the program since the total mean score from the Likert Scale fell to the "agree" category.